The relationship between falling and fear of falling among community-dwelling elderly. Issue 26 (2nd July 2021) - Chen, Wei-Cheng; Li, Yang-Tzu; Tung, Tao-Hsin; Chen, Chieh; Tsai, Ching-Yao
Abstract : Abstract: Researchers have repeatedly examined the relationship between a previous experience of a fall and subsequent fear of falling (FOF); however, few studies have investigated the effects of falling along various timelines among older adults. The objective of this study was to determine whether experiencing a fall in the previous month or the previous year led to FOF among the elderly. The National Health and Aging Trends Study (NHATS) in the U.S. collected information indicative of basic trends in the behavior of individuals aged 65 years and older. In the current study, we applied multiple logistic regression analysis of results from round 7 of the NHATS with the aim of identifying the risk factors associated with FOF among 5559 participants aged 65 years or older. FOF was reported by 48.8% of those who experienced a fall in the previous year and 46.8% experienced a fall in the previous month. The results of regression analysis revealed that after adjusting for sex, age, related chronic disease, activities of daily living, and instrumental activities of daily living, FOF was significantly associated with experiencing a fall during the previous month (OR = 2.29, 95% CI: 1.78–2.95) or during the previous year (OR = 2.60, 95% CI: 2.16–3.14). Our results indicate that experiences of falling during the previous month or the previous year were both significantly associated with a fear of falling, and caregivers should keep this in mind when dealing with community-living elderly individuals.